(3cdjdI hOefIs - (3GHf GdebaY , CHh YeQ YHO Gddg Hf GdebaY, GHf GdebaY,J (B142 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3GSJhOY efg hcfJ QLGFi ajeG TNUJ s
(3BNQgG (B:s
(3BNQ GdehLhO efg Pdc dZjQg abd eG JSJbje dg UMHJge dCfg jLJeY Ydjg YOhg hUOjbg HGdYOGhI s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B156s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs